Supply-side drivers of residential price in Malaysia: a qualitative analysis from developers' perspectives - Mohd Thas Thaker, Hassanudin *; Ariff, Mohamed * (Emerald, 2020)
Purpose: This study aims to explore the issue of residential price in Malaysia from a supply-side perspective. The views are directly obtained from medium and small-scale developers in Malaysia. Design/methodology/approach: We used the semi-structured interview for analysis purpose. The samples are from property developers (medium and small-scale developers) and a single respondent from the Malaysian National House Buyers Association. We used the judgmental sampling method to choose respondents for this study. The interview results went through content analysis in order to derive common themes, resulting in the identification of four main themes. Findings: First, developers view that the residential market is growing at a good pace, albeit slowly. However, the issue of unaffordability and construction costs remains to haunt the progress of property development in Malaysia. Second, from supply-side perspectives, there are several main reasons why the residential prices in Malaysia are uncontrollable: (1) costs of construction, (2) taxes, (3) existing units, (4) location and (5) urbanization. The third theme is the government support in catering to the needs and wants of middle- and lower-income earners. Most respondents agreed that the government has been providing low-cost houses supported by various incentives. Finally, on price control strategies for residential units, recommended suggestions are as follow: embracing different methods of construction styles, promote the uses of local materials instead of relying on imported materials, continuously review rules and regulations, provide more incentives and to build partnerships between the government and private companies on affordable housing projects. Practical implications: The research is expected to present solid findings and claimsseveral significant contributions, especially policy-wise. We believe this contribution will enrich the existing literature on residential market. The present study is also predicted to produce noteworthy findings to all stakeholders in the real-estate industry, such as potential home buyers and existing house owners to housing developers, marketers and government policy regulators, as well as academic institutions. Originality/value: This study is expected to enrich the existing literature available in the context of real-estate finance such as property price and property policy in emerging economies like Malaysia. One distinguishing factor which differentiates this study from others in the literature is the feedbacks obtained from medium and small-scale developers, therefore deemed to be more solid and reliable. The current research in real-estate finance is mainly focused on empirical analysis and we believe this study will offer a breakthrough view on the matter of residential market in Malaysia.